REGULATORY MODEL OF ARTIFICIAL INTELLIGENCE IN DIGITAL GOVERNMENT: BETWEEN SOFT LAW, ETHICS, AND THE NEED FOR BINDING LAW IN INDONESIA - Muhammad Suhardi (Ninety Media Publisher, 2026)
This study examines the regulatory model of Artificial Intelligence (AI) in Indonesia’s digital government, focusing on the relationship between ethical guidelines, soft law, and the need for binding legal regulation. The objective is to analyze the legal limitations of Indonesia’s AI Ethics Circular Letter and to formulate a stronger regulatory framework for AI use in public administration. This research employs a qualitative legal method with normative-juridical, conceptual, and regulatory-comparative approaches. Data were collected through documentary study of Indonesian legal instruments, including the AI Ethics Circular Letter, the Personal Data Protection Law, and the Electronic-Based Government System framework, supported by scholarly literature on AI regulation, soft law, public-sector AI governance, and administrative accountability. The findings show that Indonesia’s current AI governance remains at an early and transitional stage. The AI Ethics Circular Letter provides an important ethical foundation, but it lacks binding obligations, risk classification, mandatory audit mechanisms, institutional liability, sanctions, and remedies for citizens affected by AI systems. This study proposes a hybrid regulatory model that combines ethical principles with binding legal rules, public-sector-specific obligations, sectoral standards, institutional supervision, and accessible remedies. The study contributes to the development of rights-based and accountability-oriented AI governance in Indonesia’s digital government.